Analysis of Lampung Provincial Social Service website using PIECES framework - Muhammad Said Hasibuan; Andry Ferianto (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2023)
The official website of the Social Office Lampung Provincial contains news content, routine activities, and information on public services. The website has been changed from an internal point of view but does not yet know how satisfaction is based on user perceptions. As a result, users no longer want to visit the Social Office website, which is one of the problems, so it is necessary to build a measurement model for the classification of website user problems using the Framework Pieces. Previously, the reliability and validity test of the questionnaire was taken from 338 samples of respondents, then entered the data analysis stage by assessing user characteristics based on the Likert scale and class intervals. Framework Pieces succeed to classify the problems of 338 samples in the range of good and poor. For the Performance domain with a score of 3,62 (Good), the Informations or Data domain with a score of 2,57 (Poor), Economics domain with a score of 3,35 (Moderate), Control or Security domain with a score of 3,61 (Good), Efficiency domain with a score of 3,36 (Moderate), finally for Service domain with a score of 2,60 (Poor).